Controversies in the management of vesicovaginal fistula. (January 2019) - Breen, Michael; Ingber, Michael
Abstract: Achieving 100% closure and continence rate in the management of vesicovaginal fistulas remains a challenge. There is still debate about several aspects of the care including the following: How successful is conservative treatment with catheter drainage, and can it be improved with newer techniques? When is the best time to operate? What is the best surgical approach? Are interpositional flaps helpful? Is there any way to reduce the risk of future stress incontinence during the initial surgery? How long does the bladder need to be drained after surgery? What is the best way to manage radiation-induced fistulas? Where and by whom should the patient be operated?